Integrating TAM and Perceived Co-Creation towards behavioral Intention to Use Hotel Website - Ratna, Jeffry; Sharizal, Hashim; Janifer, Lunyai (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2023)
Previous studies have highlighted the importance of co-creation to enhance long–term competitive advantage for a particular digital platform. The Co-creation study has been widely used for social media platforms, but is still vague to understand the perceived of co-creation in website platforms, thus, requiring more evidence. In line with the current discussion on digital impact towards the tourism industry, this study has considered co-creation and other driven factors in the use of tourism websites. The Technology Acceptance Model (TAM) is a theory that has been constructed to comprehend an individual's intention to use current technologies and innovations TAM theoretically understands Perceived Ease of Use, Perceived Usefulness, and Perceived Enjoyment to interpret a user's behavioural Intention to Use. Therefore, this model integrates TAM with value co-creation in predicting individual intention towards the use of tourism websites. Based on convenient sampling and a selfadministered questionnaire, data from 399 respondents who used and experienced the tourism website in Sarawak were collected. PLS-SEM was utilized to evaluate the relationships and the result revealed that the perceived co-creation together with perceived ease of use did directly affect an individual intention to use a tourism website. In addition, perceived usefulness was identified as a significant mediator of that relationship. As such, this study provides beneficial insights on how the tourism industry should develop effective co-creation strategies that enhance tourism websites Therefore, expanding TAM with value co-creation may be considered as another conceptual contribution toward the empowerment of digital toward the success of tourism in the present world.